Pseudomembranous Trigonitis: A Common but Underrecognized Urological Entity - M. Stavropoulos; A. G. Papatsoris; C. Konstantinidis; M. Chrisofos (Advances in Urology)
Pseudomembranous trigonitis is the term used to describe squamous metaplastic changes of the bladder trigone, which affect nearly 40% of adult females. We present the characteristics of this underrecognized clinical entity and encourage further relevant research.